Deduction Of Living Expenses From Damages For Loss Of Future Earnings - Balan, P (Journal of Malaysian and Comparative Law, 2019)
In 1984, the law relating to damages for personal injuries and for causing death experienced significant and far-reaching changes as a result of the Civil Law (Amendment) Act (hereafter referred to as the "1984 Act"). The 1984 Act was severely criticised by lawyers, laymen and consumer associations because it removed or altered some common law principles which benefited injure persons or the dependent of deceased persons.